Accounting Certification, Educational & Reciprocity Requirements: An International Guide. - Bayes, Paul E.; Moriarity, Shane R. (The Accounting Review, 1993)
Reviews the book "Accounting Certification, Educational & Reciprocity Requirements: An International Guide," by Jack R. Fay.